Neutrophil Lymphocyte Ratio as a Prognostic Factor in Acute Pancreatitis (Journal of Chittagong Medical College Teachers' Association, 2020)
Background:  Different scoring systems are currently in use to stratify the severity of the acute pancreatitis to guide clinicians in triaging patients with the aim of improving outcomes. The Neutrophil-Lymphocyte Ratio (NLR) provides a rapid indication of the extent of an inflammatory process.  Its value to predict the severity of acute pancreatitis has not been well studied. The aim of this study was to investigate the prognostic value of the NLR in acute pancreatitis patients.Materials and methods: This hospital based observational study was conducted at Medicine ward of Chittagong Medical College Hospital (CMCH) for one year period from January 2015 to December 2015. One hundred and four adult patients with a diagnosis of acute pancreatitis who fulfilled the defined inclusion and exclusion criteria were selected for the study. After obtaining informed consent clinical interviewing and physical examination were done according to predesigned case record form. Then blood was collected within one hour of admission. After getting the result, final selection were done following exclusion criteria. The patients were arranged into three groups according to NLR tertiles. Main outcome measures were intensive Care Unit (ICU)/High Dependency Unit (HDU) admission, Length of Stay (LOS) in the hospital and in-hospital mortality.   Results: According to NLR tertiles, patients in the 3 tertile (NLR³7.6) had significantly more ICU/HDU admissions (40.6% vs. 0%), longer average LOS (7.91 vs. 4.03 days) and more death (12.5% vs. 0%) compared with those in the 1rd tertile (NLR< 3.6). The higher the NLR tertile, the Modified Early Warning Score (MEWS) also increased significantly. According to the ROC curve, NLR values were superior in predicting ICU/HDU admission and hospitalization for ³ 7 days compared to WBC and MEWS values.   Conclusion: Elevation of the NLR during admission was significantly associated with severe acute pancreatitis and is a negative prognostic indicator in acute pancreatitis. It is superior to total WBC and modified MEWS in predicting adverse outcomes of acute pancreatitis.JCMCTA 2020 ; 31 (1) : 90-95